2015
DOI: 10.1364/ao.54.00f210
|View full text |Cite|
|
Sign up to set email alerts
|

Overview of transparent optical ceramics for high-energy lasers at NRL

Abstract: In this review, we present our recent research progress at the Naval Research Laboratory in the development of highly transparent and rugged ceramic window materials such as MgAl2O4 spinel and β-SiC; high-power solid-state laser gain materials based on sesquioxide such as Yb(3+):Y2O3, Yb(3+):Lu2O3, and Ho(3+):Lu2O3; and composite ceramics in the application for high-energy lasers. Various powder synthesis/purification methods and powder post-process techniques necessary to create high-purity powders are descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Crystal photograph and transmission spectrum of LGSO:Y [47]. et al [6] produced by hot-pressing a 10% Yb:Lu 2 O 3 laser crystal pumped at 975 nm and emitting at 1080 nm presenting a slope efficiency of 74% with an output power of 16 W.…”
Section: Neodyminum (Lgso:nd) and Ytterbium-doped (Lgso:yb)mentioning
confidence: 99%
See 2 more Smart Citations
“…Crystal photograph and transmission spectrum of LGSO:Y [47]. et al [6] produced by hot-pressing a 10% Yb:Lu 2 O 3 laser crystal pumped at 975 nm and emitting at 1080 nm presenting a slope efficiency of 74% with an output power of 16 W.…”
Section: Neodyminum (Lgso:nd) and Ytterbium-doped (Lgso:yb)mentioning
confidence: 99%
“…Lutetium oxyorthosilicate (Lu 2 SiO 5 , LSO) has attracted the attention of researchers due to their favorable thermal and optical properties, which make it suitable as host materials to be used in photonics as laser media [3][4][5][6] or scintillators [7,41,59]. The main technique for producing LSO crystals is usually the CZ method.…”
Section: Lutetium Oxyorthosilicate (Lso)mentioning
confidence: 99%
See 1 more Smart Citation
“…The most important applications of YAG transparent ceramics include the high power solid state laser materials and high-temperature optical windows, etc. [1][2][3][4][5]. For such applications, materials must have good is an intrinsic material property that is known as the critical stress intensity factor at which a crack of a given size starts to grow in an unstable manner under plane strain conditions and opening mode loading (mode I).…”
Section: Introductionmentioning
confidence: 99%
“…As a common consolidation method, it is well known that hot pressing has been proven to be an effective and viable way to prepare various optically transparent non-oxide and oxide ceramics, such as ZnS, CaF 2 , Y 2 O 3 , Lu 2 O 3 , and MgAl 2 O 4 [29][30][31][32][33][34][35][36]. It has also been demonstrated that Cr 2+ :ZnSe transparent ceramics with suitable properties for laser applications can be fabricated via hot pressing [37].…”
mentioning
confidence: 99%